The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1067/mva.2001.114813
|View full text |Cite
|
Sign up to set email alerts
|

Association of intraluminal thrombus in abdominal aortic aneurysm with local hypoxia and wall weakening

Abstract: Our results suggest that localized hypoxia occurs in regions of thicker ILT in AAA. This may lead to increased, localized mural neovascularization and inflammation, as well as regional wall weakening. We conclude that ILT may play an important role in the pathology and natural history of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
359
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(387 citation statements)
references
References 45 publications
15
359
1
5
Order By: Relevance
“…15 Despite the relative oxygen perfusion of the thrombus, it may function as a barrier to oxygen transport, leading to hypoxia. 14 Other authors suggest the mural thrombus could be a protecting factor, reducing the hemodynamic stress on the AAA wall, such reduction being more marked in large and well organized thrombi, whereas it could also be found in small ones. 10 A study of 78 autopsies reported that 62% (49) of the aneurisms suffered rupture on the posterior wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Despite the relative oxygen perfusion of the thrombus, it may function as a barrier to oxygen transport, leading to hypoxia. 14 Other authors suggest the mural thrombus could be a protecting factor, reducing the hemodynamic stress on the AAA wall, such reduction being more marked in large and well organized thrombi, whereas it could also be found in small ones. 10 A study of 78 autopsies reported that 62% (49) of the aneurisms suffered rupture on the posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have focused on investigating the role of mural thrombi in the rupture of aneurisms, 14 since such thrombi may be associated with the weakening of the aortic wall. The wall beneath the thrombus is thinner, has less and more fragmented elastic fibers, and contains higher concentrations of inflammatory cells and lower concentrations of cells regulating production of matrix components (SMC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A local dilatation of the abdominal aorta may be expected to promote instability of the blood flow, and it is not unlikely that flashes of turbulence may occur during part of the cardiac cycle even during rest conditions (Yip & Yu 2001). This is believed to be beneficial, on the grounds that the presence of turbulence reduces the size of regions of flow stasis and the existence of a correlation between the presence of such regions and thrombus formation (Reininger et al 1994;Vorp et al 2001;Salsac et al 2004). Although we have no support for this, we believe that the repeated occurrence of a vessel wall loading with random small-scale fluctuations in time and space, due to the fact that during part of the cardiac cycle the flow becomes turbulent, may have a detrimental effect on the structure of the vessel wall, and thereby enhance the growth and rupture of aneurysms.…”
mentioning
confidence: 99%
“…Others underline the degeneration process that occurs in wall due to hypoxia, and ultimately weakens of the tissue [23,24].This biochemical approach is based on in vivo experiments and tries to capture the micro-changes in wall formation, which could locally affect its strength. Aforementioned transformation includes: the inflammation and neovascularization [25], proteolytic activity [26] -especially increase in elastase production [27], decrease in collagen synthesis [28][29][30] and production of abnormal collagen [29].…”
Section: Presence Of Intraluminal Thrombus and Calcifications In Aaamentioning
confidence: 99%